Now or never ebook - Evanovich, Janet (Stephanie Plum, 2024)
INSTANT #1 NEW YORK TIMES BESTSELLER The latest Stephanie Plum novel from #1 New York Times bestseller and "the most popular mystery writer alive" ( The New York Times ) Janet Evanovich. She said yes to Morelli. She said yes to Ranger. Now Stephanie Plum has two fiancés and no idea what to do about it. But the way things are going, she might not live long enough to marry anyone. While Stephanie stalls for time, she buries herself in her work as a bounty hunter, tracking down an unusually varied assortment of fugitives from justice. There's Eugene Fleck, a seemingly sweet online influencer who might also be YouTube star Robin Hoodie, masked hero to the homeless, who hijacks delivery trucks and distributes their contents to the needy. She's also on the trail of Bruno Jug, a wealthy and connected man in the wholesale produce business who is rumored to traffic young girls alongside lettuce and tomatoes. Most terrifying of all is Zoran—a laundromat manager by day and self-proclaimed vampire by night with a taste for the blood of pretty girls. When he shows up on Stephanie's doorstep, it's not for the meatloaf dinner. With timely assists from her stalwart supporters Lula, Connie, and Grandma Mazur, Stephanie uses every trick in the book to reel in these men. But only she can decide what to do about the two men she actually loves. She can't hold Ranger and Morelli at bay for long, and she's keeping a secret from them that is the biggest bombshell of all. Now or never, she's got to make the decision of a lifetime.